The importance of frontal QRS-T angle for predicting reverse dipper status in newly diagnosed hypertensive patients. (3rd October 2022) - Karakayali, M; Artac, I; Omar, T; Rencuzogullari, I; Karabag, Y; Hamideyin, S
Abstract: Background: The frontal QRS-T angle (fQRS-T angle) in electrocardiography is a new measure of myocardial repolarization, in which a higher fQRS-T angle is linked with worse cardiac outcomes. Reverse dipper hypertension is also linked to poor cardiac outcomes. The purpose of this study was to investigate the association between the fQRS-T angle and reverse dipper status in individuals newly diagnosed with hypertension who did not have left ventricular hypertrophy (LVH). Methods: The investigation recruited 171 hypertensive individuals without LVH who underwent 24h ambulatory blood pressure monitoring (ABPM). Based on the findings of 24h ABPM, the study population was categorized into the following three groups: patients with dipper hypertension, with non-dipper hypertension, and with reverse dipper hypertension. The frontal QRS-T angle was measured using 12-lead electrocardiography (ECG). Results: The fQRS-T angle in individuals with reverse dipper hypertension was substantially greater than in patients with and without dipper hypertension (510±280 vs. 280±220 vs. 390±250 respectively, p<0.001). The fQRS-T angle (OR: 1.040, 95% CI: 1.016–1.066; p=0.001) was independently associated with reverse dipper hypertension according to multivariate analysis. In receiver operating characteristic curve analysis, the fQRS-T angle to predict reverse dipper hypertension was 33.5° with 76% sensitivity and 71% specificity. Conclusion: This study showed that an increased fQRS-T angle was a predictor of reverse hypertension in newly diagnosed hypertensive patients without LVH. Funding Acknowledgement: Type of funding sources: None.